An Insulin‐Inspired Supramolecular Hydrogel for Prevention of Type 1 Diabetes. Issue 10 (9th April 2021) - Liu, Mohan; Wang, Zhongyan; Feng, Dandan; Shang, Yuna; Li, Xinxin; Liu, Jianfeng; Li, Chen; Yang, Zhimou
Abstract: Supramolecular peptide hydrogel has shown promising potential in vaccine development largely because of its ability to function both as antigen depot and immune adjuvant. Nap‐G d F d F d Y, a tetrapeptide hydrogel that has been previously reported to exhibit adjuvant effect, is inadvertently found to contain conserved peptide sequence for insulin, proinsulin, and glutamic acid decarboxylase, 3 major autoantigens for the autoimmune type 1 diabetes (T1D). At present, despite being managed clinically with insulin replacement therapy, T1D remains a major health threat with rapidly increasing incidences, especially in children and young adults, and antigen‐specific immune tolerance induction has been proposed as a feasible approach to prevent or delay T1D progression at an early stage. Here, it is reported that innoculation of Nap‐G d F d F d Y leads to complete protection of nonobese diabetic (NOD) mice from T1D development till the age of 36 weeks. Better maintenance of pancreatic islet morphology with minimal immune cell infiltration is also observed from mice exposed to Nap‐G d F d F d Y. This beneficial impact is mainly due to its facilitative role on enhancing peripheral T regulatory cell (Treg) population, shown as increased splenic Treg percentage, and function, demonstrated by maintenance of circulating TGF‐ β 1 level. Serum cytokine microarray data further implicate a "buffering" role of Nap‐G d F d F d Y on systemic inflammatory tone in NOD mice. Thus, with its versatility, applicability, and excellent potency, Nap‐G d F d F d Y is posited as a novel therapeutic intervention for T1D. Abstract : A hydrogel of Nap‐GdFdFdY containing conserved sequence of autoantigens including insulin, proinsulin, and glutamic acid decarboxylase as a novel therapeutic intervention for the autoimmune type 1 diabetes. Better pancreatic islet morphology with minimal immune cell infiltration is observed from mice with hydrogel because of enhancing peripheral T regulatory cell population and maintenance of circulating TGF‐β1 level.